15N SABRE Hyperpolarization of Metronidazole at Natural Isotope Abundance. Issue 14 (11th June 2021) - Kiryutin, Alexey S.; Yurkovskaya, Alexandra V.; Ivanov, Konstantin L.
Abstract: Signal Amplification By Reversible Exchange (SABRE) is gaining increased attention as a tool to enhance weak Nuclear Magnetic Resonance (NMR) signals. In SABRE, spin order is transferred from parahydrogen (H2 in its nuclear singlet spin state) to a substrate molecule in a transient Ir‐based complex. In recent years, SABRE polarization of biologically active substrates has been demonstrated, notably of metronidazole – an antibiotic and antiprotozoal drug. In this work, we study 15 N SABRE polarization of metronidazole at natural isotope abundance. We are able to demonstrate significant 15 N polarization reaching 15 %, which corresponds to a signal enhancement of 46, 000 at 9.4 T for the nitrogen atom with lone electron pair. Additionally, the other two N‐atoms can be polarized, although less efficiently. We present a detailed study of the field dependence of polarization and explain the maxima in the field dependence using the concept of coherent polarization transfer at level anti‐crossings in the SABRE complex. A study of spin relaxation phenomena presented here enables optimization of the magnetic field for efficient storage of non‐thermal polarization. Abstract : Robust 15 N polarization is achieved by SABRE (Signal Amplification By Reversible Exchange) polarization at an optimal ultralow magnetic field and storage at an intermediate field, as demonstrated for metronidazole at natural isotope abundance. The field dependence of polarization is explained by the analysis of level anti‐crossings of the SABRE complex, considering its finite lifetime.